Representation Ability in Mathematical Modeling Based on Learning Independence - Kharisudin, Iqbal; Radika Widiatmaka; Masrukan (Program Studi Tadris Matematika Universitas Islam Negeri (UIN) Salatiga, 2024)
This research investigates the impact of Problem-Based Learning (PBL) on students’ mathematical representation abilities within the context of mathematical modeling, with a particular focus on the role of learning independence. The research employs a mixed-method sequential explanatory model to analyze the effectiveness of Problem-Based Learning and to categorize students’ abilities and independence levels. Conducted with class XI TL 2 at SMAN 1 Mranggen during the 2023-2024 academic year, the findings reveal that PBL significantly enhances students’ mathematical representation abilities. Moreover, learning independence is identified in two distinct categories–high and medium–which correspond with similar levels of representation ability. Students’ mathematical representation ability has two categories, namely high and medium. These insights underscore the importance of self-directed learning in fostering mathematical comprehension and skills.